PERAN DAN STRATEGI KELOMPOK âKOTAK KOSONGâ DALAM PILKADA CALON TUNGGAL KABUPATEN PATI TAHUN 2017: STUDI PENDAHULUAN - Darmawan, Ikhsan (JWP (Jurnal Wacana Politik), 2017)
Simultaneous local election 2017 which was held in February 15th, 2017 remains an interesting political phenomenon. From 101 areas (province, municipality, and city) that held local elections, there are 9 (nine) areas whose local election consist of single candidate. The most interesting case is Local Election in Pati. Compared with other eight areas, the amount of votes gained by âkotak kosongâ in Local Election in Pati is the highest among the others. Besides that, unlike other seven areas, in Pati there is a group that propose choice of âkotak kosongâ like in Buton Municipality. This article tries to answer question: âHow are the strategies and roles of group of âkotak kosongâ cause the number of votes of âkotak kosongâ gain the highest number of votes among eight other areas? This research uses the qualitative approach with the method of data collections are: depth interviews, observation, and collecting news related from internet. This research reveals that the roles of group of âkotak kosongâ are focusing on the specific isu and benefiting their members, increasing their level, and using their power. Besides that, the group of âkotak kosongâ used strategies, such as using lobby strategy, opening the access to policy makers and mobilizing their resources, mobilizing voters, controlling information to voters, and doing advocacy. Â Â